Penguatan Implementasi Kurikulum Merdeka Setelah Masa Post Covid Pada Guru Ekonomi MGMP Provinsi Jawa Tengah - Mulyono, Kemal Budi; Rahman, M. Fathur (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2024)
This article aims to support the government's policy regarding the implementation of the Freedom Curriculum, which is provided to the Council of Economics Subject Teachers in Central Java Province as an additional option for the recovery of learning during 2022-2024. In this service, workshops and training related to the implementation of the Freedom Curriculum are conducted, with a focus on utilizing technology and community-based strategies and platforms. These are being developed for the implementation of the Freedom Curriculum. The outcome of this dedication is that each teacher can comprehend the concept of the Freedom Curriculum implementation well. Therefore, it is expected that all stakeholders involved in this implementation can optimize its utilization as an effort for post-pandemic learning recovery.